Causation: the basis for pharmacovigilance - Edwards, Ivor Ralph (Henry Stewart Talks, 2023)
Adverse drug reactions, Causation, Epidemiology, WHO method, Naranjo method, Aronson and Ferner guidelines, Scientific norms